The Impact of Debt Financing on Financial Performance and Business Risk at PT PLN (Persero) - Arifah Zahirani; Aisyah Putri; Saddam Arafit Siregar; Henny Andriyani Wirananda; Indra Fauzi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study analyzes the effect of debt financing on financial performance and business risk at PT PLN (Persero) during the 2019–2024 period. Debt financing is an important source of capital for PLN in supporting the development of national electricity infrastructure. Secondary data in the form of financial reports are analyzed using financial ratios such as Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The results of the study indicate that well-managed debt financing has a positive impact on the company's financial performance, marked by an increase in the profitability ratio and stability of the capital structure. However, risk management is still needed to avoid excessive financial burdens that can increase business risk. PLN's efforts to reduce debt balances and manage financing efficiently have succeeded in increasing the company's net profit. This study provides strategic recommendations for PLN management in maintaining a balance between the use of debt financing and risk control to support the company's sustainability and growth.